Acute effects of supramaximal loaded back squat activation on countermovement jump performance, muscle mechanical properties, and skin surface temperature in powerlifters - Perenc, Dawid; Stastny, Petr; Urbański, Robert; Krzysztofik, Michał (European journal of sport science, 2025)
This study aimed to investigate the effects of performing either eccentric-only (ECC) or eccentric-concentric (ECC-CON) back squats (BS) with a supramaximal load on countermovement jump (CMJ) performance. Changes in front thigh skin surface temperature and mechanical properties (oscillation frequency and stiffness) of the vastus lateralis were also examined. Fourteen male powerlifters participated in this study (age: 22.5 ± 2.3 years, body weight: 84.2 ± 11.1 kg, height: 178 ± 7 cm, training experience: 5.4 ± 1.6 years, BS one-repetition maximum [1RM]: 177 ± 22.8 kg). The experimental sessions included 2 sets of 2 BS at 110% 1RM of either ECC-CON (load distributed by half on the barbell [55%] and on weight releasers [55%]) or ECC (only eccentric phase of BS) and CTRL with no CA applied. CMJ performance, mechanical properties, and skin surface temperature were measured before and at the third, sixth, ninth, and 12th min. After each protocol, only the ECC-CON condition led to a significant increase in CMJ height after individual optimal rest time compared to pre-CA (38.1 ± 5.2 vs. 39.8 ± 5.0 cm; p = 0.003; effect size [ES] = 0.32; Δ = 4.9 ± 5.0%) with a significant rise in skin surface temperature (32.98 ± 1.24 vs. 33.69 ± 0.96°C; p = 0.006; ES = 0.62; Δ = 2.2 ± 2.6%) and no significant changes in mechanical properties of the vastus lateralis. The ECC-CON condition led to a significant acute improvement in CMJ height and an increase in front thigh skin surface temperature among powerlifters. The ECC-CON supramaximal lower limb PAPE protocol should be effectively used among males representing high levels of lower limb muscle strength (>2 × body mass).
Keywords: dospělí; kosterní svaly; Weight Lifting; Skin Temperature; post‐activation potentiation; Adult; mladý dospělý; Resistance Training; svalová síla; Thigh; Athletic Performance; lidé; Quadriceps Muscle; weight releasers; Muscle, Skeletal; Muscle Strength; post‐activation performance enhancement; biomechanika; muscle strength; Male; Young Adult; stehno; accentuated eccentric loading; sportovní výkon; vzpírání; mužské pohlaví; čtyřhlavý sval stehenní; power output; teplota kůže; odporový trénink; Biomechanical Phenomena; Humans